Different reference populations use in children and adolescents main nutritional problems diagnosis - Pajuelo, Jaime (2009)
Introduction: The existence of different reference populations for overweight and obesity diagnosis in children warrants comparative analysis. Objectives: To determine existing differences in nutritional diagnosis using different reference populations. Design: Descriptive, comparative and transversal study. Setting: Hospital Dos de Mayo Growth and Development Section and a Lima Metropolitan State School. Participants: Male and females children aged between 2 and 17 years. Interventions: Two hundred and nineteen children 2 to 5 year-old were studied, as well as 1141 girls and adolescents between 9 to 17 years. In the first group chronic malnutrition (height / age < -2 SD) and obesity (weight/ height > +2 SD) diagnosis was done according to the 1983 National Center for Health Statistics (NCHS) and 2005 World Health Organization (WHO) references. In the second group body mass index (BMI) was used for overweight and obesity diagnosis, based on Must, Cole and WHO references, and using between 85 and 95 and greater than 95 percentile for overweight and obesity diagnosis criteria. Main outcome measures: Prevalence of chronic malnutrition, overweight and obesity. Results: In children between 2 and 5 years, chronic malnutrition prevalence was respectively 1,8% (NCSH) and 5,9% (WHO), and 4,6% (NCSH) and 9,1% (WHO) for obesity. In the 9 to 17 years group, the above 85p prevalence was 30,3% (Must), 33% (Cole) and 35,2% (WHO); for overweight, respectively 21% (Must), 26,3% (Cole) and 18% (WHO), and for obesity 9,3% (Must), 6,7% (Cole) and 17,2% (WHO). Conclusions: The results differ depending on the reference used. The WHO reference identifies higher prevalence of chronic malnutrition and obesity in the preschool group. The same applies to the group of girls and adolescents in regard to overweight and obesity. All differences found reflect a statistical approach rather than a biological criterion.